Of my own making : a memoir - Burke, Daria (Legacy Lit, 2025)
"Daria Burke's childhood growing up under the shadow of an absent father and a mother debilitated by drug addiction was marked by neglect and poverty. Despite these fractured beginnings, she forges a triumphant path out of Detroit and into fashion's C-Suite. After ten years of therapy, she believes her healing journey is complete. When she discovers a photograph of the car accident that she believes altered the course of her early life, Burke is forced to confront the parts of her childhood she had avoided. This discovery sparks a four-year immersion into neuroplasticity, epigenetics, the impact of adverse childhood experiences on early brain development and ultimately, why some of us remain stuck in past trauma while others experience Post Traumatic Growth... More than a story of personal triumph, Of My Own Making is a soulful and scientific exploration of the power to shape one's destiny."--